On the conjugacy classes of split metacyclic 2-Groups of class two - Sheila Hangovan; Nor Haniza Sarmin, author; Universiti Teknologi Malaysia. Fakulti Sains. Jabatan Matematik (Johor Bahru, Johor : Penerbit Jurnal Akademik, 2011)
Bibliography: p. 6.